Work-life balance policy and practice in Nigeria - Ugo Chuks Okolie; Akpomuvire Mukoro; Atare Otite (Journal of Social Studies (JSS), 2023)
It believes that giving people the freedom to manage their own work and make decisions improves their performance. Quality of work life aims to instill a culture of work commitment within organizations and society at large in order to improve job satisfaction and employee performance. The fulfillment of seven needs health and safety needs, economic and family needs, social needs, esteem needs, actualization needs, knowledge needs, and aesthetic needs ensures the quality of work-life. Organisations in Nigeria have a reputation for ignoring decent work practices and embracing precarious working conditions to the detriment of the populace. The country's organisations appear to be primarily concerned with increasing profits at the expense of employee welfare. The purpose of this study is to investigate work-life balance policy and practice in Nigeria. To gather data, relevant information was extracted from conference papers, public records, textbooks, journals, and other sources. According to this study, a work-life balance requires planning, and the most prosperous people have found happiness in both the short- and long-term by developing a barometer to help them manage their lives. This study recommends among other things that availability and use of work-life balance practices, when provided in the context of supervisor and organisational support can reduce work-life conflict and increase positive appraisals of one’s organisation. These effects are often associated with employee attitudes such as increased job satisfaction and enhanced control over their work schedule.